Instruction Using Social Media in Global Higher Education (Journal of Education and Development, 2019)
The technological revolution of the past two decades has changed communication, higher education, and the global society. As a result, there exists a wide gulf between the unlimited use of technology and higher education, particularly with respect to digital communications between professors and students. Web 2.0 digital technologies convey information in a different manner than before and allow for interaction with distance participants. Personal use of digital technologies for social media communication is one thing; social media use by professors for communication with students is another. Both aspects should be examined in detail to determine the future directions for global learning.